2017
DOI: 10.1186/s13717-017-0083-7
|View full text |Cite
|
Sign up to set email alerts
|

Plant species composition and diversity depending on piospheres and seasonality in the southern rangelands of Kenya

Abstract: Introduction: Scarcity of water in the rangelands of Kenya has led to the introduction of piospheres. Previous research has however produced contrasting results on the effects of piospheres and seasonality on ShannonWiener's diversity index, and therefore, this information is still deficient. In this study, the impact of these piospheres on plant species composition, diversity, and richness was assessed. Methods: Vegetation sampling was done during both the long rains (April) and the dry season (August). Three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…2005, Jawuoro et al. 2017), likely because of its ability to produce both stolons and rhizomes (Dong and de Kroon 1994). We postulate that these opposite responses can be attributed to variation in dominant plant reproductive and growth traits whose trade‐offs become apparent across a gradient ranging from high competition (high abiotic resources and low herbivory) to elevated stress (low abiotic resources and high herbivory).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2005, Jawuoro et al. 2017), likely because of its ability to produce both stolons and rhizomes (Dong and de Kroon 1994). We postulate that these opposite responses can be attributed to variation in dominant plant reproductive and growth traits whose trade‐offs become apparent across a gradient ranging from high competition (high abiotic resources and low herbivory) to elevated stress (low abiotic resources and high herbivory).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, we found the opposite pattern on arid sandy soils; Cynodon dactylon, a globally important grazing species, was the most common species on 60% of water source transects. C. dactylon is able to propagate in heavily grazed areas (van der Westhuizen et al 2005, Jawuoro et al 2017, likely because of its ability to produce both stolons and rhizomes (Dong and de Kroon 1994). We postulate that these opposite responses can be attributed to variation in dominant plant reproductive and growth traits whose trade-offs become apparent across a gradient ranging from high competition (high abiotic resources and low herbivory) to elevated stress (low abiotic resources and high herbivory).…”
Section: Q3 Which Plants Have Positive and Negative Responses Tomentioning
confidence: 97%
See 2 more Smart Citations
“…However, with increasing grazing intensity, vegetation coverage decreased dramatically but had no effects on species richness, Shannon-Wiener index, and Pielou evenness index in Gangcha County, Qinghai Province (Chu et al, 2019). In the southern rangelands of Kenya, heavy grazing decreased species diversity, richness, and evenness (Jawuoro et al, 2017). Dingaan et al (2016) found no dramatic difference in species richness between L.G.…”
Section: Effects Of Grazing Intensity On Plant Community Assemblymentioning
confidence: 92%